The Transformation of Islamic Education Curriculum Development Models Towards the Era of Society 5.0 - Sari, Indri Via Yunita; Kamila, Estiti Rifngatul; Kholis, Nur (Journal of Educational Research and Practice, 2023)
Facing the era of society 5.0 which is characterized by advances in industrical technology to facilitate the needs of human life, Islamic education needs to transform the components of learning system, one of which is curriculum. With various models of islamic religion education curriculum that can be aplied, this is a challenge as well as an opportunity in realizing the succes of learning in the 5.0 society era. This study aims to identify a model for developing an Islamic religious education curriculum and to analyze its implementation in facing the era of society 5.0. Research in this case using the method of literature study. Based on the results of the author’s analysis, it is known that all existing curriculum development models (action research models, administrative and so on) can be applied in learning islamic religious education in the era of society 5,0. However, in the development of Islamic religious education curriculum, we still sanad to importance of scientific knowledge by continuing to carry out direct learning with teachers in addition to learning with technology in the 5.0 society era. On other hand, teachers must upgrade their cognitive, affective and skills possessed so that they are ready to accompany students in the era of society 5.0.